Effect of training and compensation of employee performance medicated by job satisfaction - Diliantari, Komang Richa Diah; Dewi, I Gst. A. Manuati (International research journal of management, IT and social sciences, 2019)
The purpose of this study was to determine the impact of training and compensation on employee performance through employee job satisfaction by using 125 respondents as a basis for research analysis. The results showed that training and compensation had a significant positive effect on employee performance and job satisfaction is known to mediate the relationship of training on employee performance and compensation on employee performance at Belmond hotel partially. The findings in this study provide the implication that to improve employee performance in order to achieve the company’s expected targets, the things that need to be considered in terms of job satisfaction with performance is the way employees can see opportunities and rewards, the nature of the job itself, supervision or supervisor, benefits, operational conditions of employees, and coworkers as a positive incentive to work. Improvements in knowledge and skills relevant to the work in each department as well as experienced in the training also need to be considered. Increasing compensation for salaries, benefits and incentives can increase their understanding of satisfaction with work results achieved by an employee.